The Cunning Fox and Other Stories - Editorial Board (Nestling Books Publishing & Distributors (p) Ltd., Chennai, 2016)
The wonderful stories carry children into the land of fantasy, adventure, magic, fairies and animals. These stories will bring a smile on their faces.
The Cunning Fox, The Bundle of Sticks, The Ant and the Grasshopper, The Peaceful Monkey, The Generous Lion.